Mayan Urbanism: Impact on a Tropical Karst Environment. (April 2023) - Brenner, Mark
Deevey et al.'s (1979) Mayan Urbanism: Impact on a Tropical Karst Environment combined paleo-demographic data from the Lowland Maya region, obtained from archaeological survey and test-pitting, with paleolimnological data derived from local lakes, to evaluate the environmental impacts of long-term, ancient Maya agro-engineering activities in the region. The interdisciplinary approach to studying human-environment interactions was novel at the time and paved the way for many subsequent hybrid Earth Science/Archaeology projects in the Maya area.